Optimization of Role of Coach in The Basic Value of Civil Apparatus Actualization Professionals Candidate Apparatus on Civil Government in The City of Samarinda - Endang Tri Wahyuningsih; Dewi Sartika (International Journal of Science and Society, 2020)
This study aims to find out how to optimize the role of coaches to actualize the basic values ​​of Candidate Civil Servants in Samarinda City Government Environment. The research method used is a quantitative approach, where data collection is obtained from primary data through a survey with a questionnaire instrument for respondent coaches and trainees. A total of six categories of questions were addressed to trainee respondents and six open questions addressed to coaches. The results of the study after analysis are that the role of the coach in carrying out the role of coaching and mentoring towards participants is quite high. However, some things that need to be optimized from all of these categories. respondents who answer sometimes, sometimes not as many as 1 to 3 people. Keywords: coach, the actualization of the basic values of the profession, Civil Servants Candidate, Regional Government of Samarinda City